First-in-Human Study to Assess the Safety and Feasibility of the Bashir Endovascular Catheter for the Treatment of Acute Intermediate-Risk Pulmonary Embolism. (January 2021) - Sista, Akhilesh K.; Bhatheja, Rohit; Rali, Parth; Natarajan, Kannan; Green, Philip; Piazza, Gregory; Comerota, Anthony J.; Parikh, Sahil A.; Lakhter, Vladimir; Bashir, Riyaz; Rosenfield, Kenneth
Abstract : Background: The Bashir Endovascular Catheter (BEC) is a novel pharmaco-mechanical device designed to enhance thrombolysis by increasing the exposure of thrombus to endogenous and exogenous thrombolytics. The aim of this prospective, multicenter, single-arm study was to evaluate the feasibility and initial safety of the BEC in patients with acute intermediate-risk pulmonary embolism (PE). Methods: Patients with symptomatic PE and right ventricular to left ventricular diameter ratio ≥0.9 as documented by computer tomography angiography were eligible for enrollment. The primary safety end points were device related death or adverse events, and major bleeding within 72 hours after BEC directed therapy. Results: Nine patients were enrolled across 4 US sites. The total dose of r-tPA (recombinant tissue-type plasminogen activator) was 14 mgs in bilateral PE and 12 mgs in unilateral PE over 8 hours delivered via the expanded BEC. At 30-day follow-up, there were no deaths or device-related adverse events. At 48 hours post-BEC therapy, the right ventricular to left ventricular diameter ratio decreased from 1.52±0.26 to 0.97±0.06 ( P =0.0009 [95% CI, 0.33–0.82]; 37.0% reduction). Thrombus burden as measured by the Modified Miller Index decreased from 25.4±5.3 to 16.0±4.0 ( P =0.0005; [95% CI, 5.5–13.4]; 37.1% reduction). Conclusions: In this early feasibility study of the BEC for intermediate-risk PE, there were no deaths or device-related adverse events and a significant reduction in right ventricular to left ventricular diameter ratio and thrombus burden. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT03927508. Abstract : Supplemental Digital Content is available in the text.